Slow light and slow acoustic phonons in optophononic resonators - Villafañe, Viviana Daniela (2016)
Slow and confined light have been exploited in optoelectronics to enhance light-matter interactions. Here we describe the GaAs/AlAs semiconductor microcavity as a device that, depending on the excitation conditions, either confines or slows down both light and optically generated acoustic phonons. The localization of photons and phonons in the same place of space amplifies optomechanical processes. Picosecond laser pulses are used to study through time-resolved reflectivity experiments the coupling between photons and both confined and slow acoustic phonons when the laser is tuned either with the cavity (confined) optical mode or with the stop-band edge (slow) optical modes. A model that fully takes into account the modified propagation of the acoustic phonons and light in these resonant structures is used to describe the laser detuning dependence of the coherently generated phonon spectra and amplitude under these different modes of laser excitation. We observe that confined light couples only to confined mechanical vibrations, while slow light can generate both confined and slow coherent vibrations. A strong enhancement of the optomechanical coupling using confined photons and vibrations, and also with properly designed slow photon and phonon modes, is demonstrated. The prospects for the use of these optoelectronic devices in confined and slow optomechanics are addressed.